Dental and alveolar arch widths in normal occlusion and class III malocclusion - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2005)
The aim of this study was to compare the transverse dimensions of the dental arches and alveolar widths of Class III malocclusion group with a group of untreated normal occlusion subjects. This study was performed using measurements on dental casts of 150 normal occlusion (mean age, 21.6 +/- 2.6 years) and 100 Class III malocclusion (mean age, 15.4 +/- 2.2 years) subjects. Independent samples Mest was applied for comparing the groups. The findings of this study indicated that the mandibular intercanine and intermolar alveolar widths were significantly larger in the Class III group when compared with the normal occlusion sample (P < .001). Maxillary interpremolar, intermolar widths and all maxillary alveolar width measurements were significantly narrower in the Class III group (P < .001). In addition, the lower canine and premolar alveolar width measurements were also statistically significantly larger in the normal occlusion group when compared with the Class III malocclusion group (P < .001). Subjects with Class III malocclusion tend to have the maxillary teeth inclined to the lingual and mandibular teeth inclined to the buccal direction because of the restriction of maxillary growth and development according to dental arch width measurements. Therefore, rapid maxillary expansion should be considered before or during the treatment of a Class III patient with or without face-mask therapy.
Keywords: class III; normal occlusion; dental width; alveolar arch width; TOOTH-SIZE; DIVISION-1 MALOCCLUSION; CLASS-I; FORM; AGE; DENTITION; MAXILLARY